2016
DOI: 10.1038/nchem.2590
|View full text |Cite
|
Sign up to set email alerts
|

Deep-hole transfer leads to ultrafast charge migration in DNA hairpins

Abstract: Charge transport through the DNA double helix is of fundamental interest in chemistry and biochemistry, but also has potential technological applications such as for DNA-based nanoelectronics. For the latter, it is of considerable interest to explore ways to influence or enhance charge transfer. In this Article we demonstrate a new mechanism for DNA charge transport, namely 'deep-hole transfer', which involves long-range migration of a hole through low-lying electronic states of the nucleobases. Here, we demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 39 publications
5
70
0
Order By: Relevance
“…50 Our experiments do not provide information about the bases responsible for electron ejection. Regardless, electron holes are expected to be ultimately located on the guanines, possibly after charge transport [51][52][53][54] and undergo deprotonation on the ns timescale. 38 It has been reported that the deprotonated guanine radicals produced in photosensitization experiments survive for hundreds of ms. 23 Moreover, the latter study concerning duplexes with mixed AT/GC sequences correlated a transient absorption decay occurring within a few ms with the reaction intermediate [(8-OH-G):C] leading to 8-oxoG.…”
Section: View Article Onlinementioning
confidence: 99%
“…50 Our experiments do not provide information about the bases responsible for electron ejection. Regardless, electron holes are expected to be ultimately located on the guanines, possibly after charge transport [51][52][53][54] and undergo deprotonation on the ns timescale. 38 It has been reported that the deprotonated guanine radicals produced in photosensitization experiments survive for hundreds of ms. 23 Moreover, the latter study concerning duplexes with mixed AT/GC sequences correlated a transient absorption decay occurring within a few ms with the reaction intermediate [(8-OH-G):C] leading to 8-oxoG.…”
Section: View Article Onlinementioning
confidence: 99%
“…[1][2][3] Researchers have demonstrated how to use Watson-Crick base pairing rules to program the selfassembly of nucleic acids into a diverse array of shapes and structures, and it is now possible to imagine creating a wide range of functional motifs. 4,[8][9][10] Moreover, these various regimes and the transitions between them are known to be sensitive to nucleobase sequence, length, and charge injection energy. [4][5][6][7] Nucleic acids display unusual complexity in their charge transport properties, with mechanisms that range from coherent tunneling at short distances, to incoherent hopping at long distances, and coherent ballistic charge transfer via the flickering resonance mechanism at intermediate distances.…”
Section: Introductionmentioning
confidence: 99%
“…We note, however, that the reversible hole injection discussed above may complicate the dynamics, and the true mechanism is likely more subtle. 42 Hole Trapping Dynamics. The results of the kinetic modeling of the TA data off er insight into the hole transport dynamics and hole location in the EG-and G-sequences.…”
mentioning
confidence: 99%